Enhanced Supercapacitance of Hydrous Ruthenium Oxide/Mesocarbon Microbeads Composites toward Electrochemical Capacitors - Changzhou Yuan; Linrui Hou; Diankai Li; Long Yang; Jiaoyang Li (International Journal of Electrochemistry)
A facile hydrothermal strategy was proposed to synthesize RuO2⋅nH2O/mesocarbon microbeads (MCMBs) composites. Further physical characterizations revealed that RuO2⋅nH2O nanoparticles (NPs) were well dispersed upon the surfaces of the MCMB pretreated in 6 M KOH solution. Electrochemical data indicated that the RuO2⋅nH2O/MCMB composites owned higher electrochemical utilization of RuO2 species, better power property, and better electrochemical stability, compared with the single RuO2 phase. The good dispersion of RuO2⋅nH2O NPs and enhanced electronic conductivity made the H+ ions and electrons easily contact the RuO2⋅nH2O phase for efficient energy storage at high rates.